ANALISIS KEMAMPUAN NUMERASI DAN MINAT BELAJAR SISWA MELALUI MODEL GAME BASED LEARNING BERBASIS WORDWALL - Putriana Ramadhani; Laisya Okta Preyera; Susanti; Destrinelli; Risdalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low levels of students' numeracy skills and learning interest in mathematics present a challenge in elementary education. This study aims to improve numeracy skills and learn-ing motivation through the implementation of a Wordwall-based Game Based Learning (GBL) model. The research employed a mixed-method approach, combining quantitative methods using numeracy tests and learning interest questionnaires with qualitative met-ods such as classroom observations and interviews. The study involved 19 fifth-grade students at SD Negeri 80 Kota Jambi. The results showed a steady increase in the average numeracy scores, from 63.2 in the first meeting of cycle 1 to 81.3 in the second meeting of cycle 2. Likewise, the average learning interest score increased from 68.5 to 84.5. These findings indicate that interactive media like Wordwall not only enhances students’ contextual understanding of mathematical concepts but also fosters greater motivation and engagement in learning. It can be concluded that the Wordwall-based GBL model is effe-tive in improving both numeracy skills and learning interest through an enjoyable ap-proach aligned with the characteristics of 21st-century learners.